Negotiating the impact of international experiences on professional identity development: A case study of Chinese college English teachers - Zhang, Fengjuan; Wang, Jing (Frontiers in Psychology, 2022)
This study traced changes in Chinese college English teachers’ professional identities as a result of participating in international professional development programs and examined how the teachers negotiated their professional identities upon returning to China. Five college English teachers with at least 10 months of overseas professional development experience took part in the study. Data were collected through semi-structured interviews and relevant documents. It was found that international experiences had a large impact on the teachers’ professional identity construction by empowering them to develop multifaceted identities as language teaching professionals, university academics, and change agents. The teachers’ reconstruction of professional identities upon their return to China was not a linear and smooth process. Rather, it was a dynamic process of negotiating with the constraints of the personal and professional contexts to which the teachers returned. The study sheds light on the identity development of internationally trained language teachers, contributing to an increased understanding of the impact of international experiences on the professional development of second language teachers in similar contexts. It has implications for study abroad programs and home institutions regarding how to support the long-term professional development of returnee teachers.